Relationship between butyrylcholinesterase activity and hepatic transaminases: a cross-sectional study in agricultural workers from Peru - Emily Ortiz-Delgado; Guido Bendezu-Quispe; Fernando Soncco-Llulluy; Jair Li; Jaime Rosales-Rimache (Journal of Occupational Medicine and Toxicology)
Abstract Introduction Chronic exposure to pesticides causes various adverse health effects, mainly at a neurological level. However, there is little evidence focused on liver tissue injury and transaminase activity as indicators of effect. Methods A cross-sectional study was designed based on medical-occupational records of workers from an agro-export company in Peru to associate the levels of butyrylcholinesterase (BChE) transaminases (ALT and AST). Occupational medical records were reviewed to obtain demographic and occupational information and laboratory values of BChE activity and transaminases. Results We evaluated 459 records, and 69.9% were men. The mean age was 34.9 ± 11.5 years. BChE, ALT, and AST levels were 6238.8 ± 709.1 U/l, 34.4 ± 12.5 U/l, and 22.4 ± 8.5 U/l, respectively. The proportion of inhibited BCHE and elevated transaminase levels was 15.3% and 21.6%, respectively. We found a significant association between BChE inhibition and elevation of transaminases (AST: PR = 0.798, 95%CI: 0.716–0.889; ALT: PR = 0.419, 95%CI: 0.239–0.736). Conclusion The potential usefulness of transaminases is shown as a biomarker of exposure and monitoring in occupational health programs for the agro-industry.